2016
DOI: 10.1080/19443994.2015.1093554
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of synthetic and natural coagulants for silver nanoparticles removal from wastewater

Abstract: A B S T R A C TUse of silver nanoparticles is increasing in different packaging material as disinfectant to protect food and pharmaceutical products. Its use has raised the contamination risk of fresh water and human exposure can cause serious problems. The coagulation/flocculation process can be an attractive option for silver nanoparticles removal at small-scale treatment just after its use. Four coagulants, aluminum sulfate, ferric chloride, Ocimum basilicum, and Hibiscus esculentus (synthetic and natural) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The present data revealed that the removal efficiency of AgNPs increase by increasing the amounts of MWCNTS (Table 1). This result was agreed with [42] who use four synthetic and natural coagulants as attractive option for AgNPs removal at small-scale, the authors observed that the removal percent of AgNPs increases with the increase in coagulant doses, and also in agreement with [43] Figure 3 and Table 2 Values within columns with no common superscript differ significantly (P ˂ 0.05). …”
Section: Effect Of Mwcnts On Adsorption Of Agnpssupporting
confidence: 80%
“…The present data revealed that the removal efficiency of AgNPs increase by increasing the amounts of MWCNTS (Table 1). This result was agreed with [42] who use four synthetic and natural coagulants as attractive option for AgNPs removal at small-scale, the authors observed that the removal percent of AgNPs increases with the increase in coagulant doses, and also in agreement with [43] Figure 3 and Table 2 Values within columns with no common superscript differ significantly (P ˂ 0.05). …”
Section: Effect Of Mwcnts On Adsorption Of Agnpssupporting
confidence: 80%
“…Many methods have been developed to remove silver nanoparticles, including the use of microorganisms and coagulation [20][21][22][23]. Various processes based on adsorption have been used for the removal of metallic nanoparticles, using materials such as chitosan [24], lignin [25], spent adsorbent [26], biochar [27,28], or biomass waste [29].…”
Section: Introductionmentioning
confidence: 99%
“…ENPs may bioaccumulate in important parts of the body, such as the brain, lungs, and/or liver, which can be harmful to health [5]. For example, Ag-NPs are likely to cause irreversible damage to the human body, such as changes in neurotransmitter levels and liver enzymes, and affect the human immune system [6].…”
Section: Introductionmentioning
confidence: 99%
“…As the knowledge on NPs becomes clear, methods for treating NPs in water (e.g., coagulation/flocculation/sedimentation, membrane filtration, adsorption, and oxidation) have been actively explored [5,[14][15][16]. For example, Jiang et al [15] found that the fluoroethylene fluoride microporous membrane is a new type of environmentally friendly industrial microporous membrane with a relatively low cost, exhibiting a ENP removal rate of up to 94.8%.…”
Section: Introductionmentioning
confidence: 99%